Rancang Bangun Timbangan Digital Load Cell Berkapasitas 20 kg Berbasis Modul HX711 - Sri Hartanto; Aryaniko Saputra (Teknik Elektro Universtias Krisnadwipayana, 2024)
Digital scales are electrical devices that are used to weigh or determine weight. There are various sizes of scales made from various materials. In this research, digital scales are made using load cell data, which will be processed by the Arduino Nano via a driver that has a data size of 24 bits and the HX711 Module, which functions to convert the potential quantity on the load cell into digital data that the Arduino Nano can read so that it appears on the Liquid Crystal Display (LCD) screen. The Arduino Nano in this research is tasked with comparing data from the load cell with the set-point values that have been entered. If the weight read on the load cell is the same as the set-point value, the Arduino Nano processes or sends instructions to the circuit, which reads the weight value of the object that has been weighed so that it appears on the LCD screen. The aim of this research is to determine the accuracy of digital scales using load cells whose data is processed by Arduino Nano. The measurements were carried out 12 times, and the measurement results obtained an accuracy presentation of 99.039% and an error presentation of 0.961%.